THE USE OF SMALL GROUP DISCUSSION TECHNIQUE TO IMPROVE STUDENTS' READING COMPREHENSION - Gerry Kasiha; Paula Hampp; Tirza Kumayas (Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this study was to find out whether the use of Small Group Discussion Technique is able to improve students’ Reading Comprehension. The students at SMP Anugerah Tondano in academic year 2021/2022 were chosen as the subject of this study, specified to the eighth grade that consisted 14 students. This research used pre-experimental design with one group pre-test and post-test. This study consisted in five meetings. First the researcher gave a pretest second, treatment and the last posttest. The technique in collecting data used test as instrument in form of multiple choice test consisted with 10 numbers. The result of this study found that the use of Small Group Discussion was effective in improving students’ Reading Comprehension where post-test was higher than pre-test. The mean score pre-test was 4,14 and the mean score of post-test was 6.64. It can be stated that the use of Small Group Discussion is considered effective to improve students’ Reading Comprehension.